2018
DOI: 10.1002/open.201700197
|View full text |Cite
|
Sign up to set email alerts
|

Translational Chemistry Meets Gluten‐Related Disorders

Abstract: Gluten‐related disorders are a complex group of diseases that involve the activation of the immune system triggered by the ingestion of gluten. Among these, celiac disease, with a prevalence of 1 %, is the most investigated, but recently, a new pathology, named nonceliac gluten sensitivity, was reported with a general prevalence of 7 %. Finally, there other less‐prevalent gluten‐related diseases such as wheat allergy, gluten ataxia, and dermatitis herpetiformis (with an overall prevalence of less than 0.1 %). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 119 publications
(105 reference statements)
0
21
0
Order By: Relevance
“…They are named according to clinical symptoms and immunological response as wheat allergy, celiac disease (CD), gluten ataxia, dermatitis herpetiformis and non-celiac gluten sensibility. 1 In wheat, gliadin and glutenin are the major components of gluten. 2 It is known that humans do not fully degrade gliadin and after its digestion, some large peptic fragments remain unprocessed.…”
Section: Accepted Manuscript 3 Backgroundmentioning
confidence: 99%
“…They are named according to clinical symptoms and immunological response as wheat allergy, celiac disease (CD), gluten ataxia, dermatitis herpetiformis and non-celiac gluten sensibility. 1 In wheat, gliadin and glutenin are the major components of gluten. 2 It is known that humans do not fully degrade gliadin and after its digestion, some large peptic fragments remain unprocessed.…”
Section: Accepted Manuscript 3 Backgroundmentioning
confidence: 99%
“…Interestingly, other autoantibodies may also be involved, especially in extraintestinal manifestations, such as anti-ganglioside, anti-synapsin I and anti-actin antibodies [ 18 ]. Patients with CD present either typical or atypical symptoms [ 19 ] and CD is believed to perpetuate other maladies and often presents simultaneously with other autoimmune diseases [ 20 , 21 , 22 , 23 ]. Despite the great progress in CD research, new key emerging findings suggest previously unknown features of CD pathogenesis, for example at the transcriptome level of immune cells [ 24 ].…”
Section: Gluten-related Disorders and Celiac Diseasementioning
confidence: 99%
“…The fact that genetic susceptibility is not determinant for the presentation of CD (30–40% of the population have the required genotype but the prevalence of CD is only about 1%) has prompted research to discover what other factors can predict the clinical manifestation of the disease [ 21 ]. For example, there is enough evidence to suggest that the gut microbiota (especially Bacteria) plays a role in the onset and clinical manifestations of CD [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and probably other GRD.…”
Section: Grd and The Gut Microbiotamentioning
confidence: 99%
“…The 33-mer gliadin peptide, LQLQPFPQPQLP 69 YPQPQLP 76 Y PQPQLP 83 YPQPQPF, is a proteolytical resistant fragment of gliadin, which is a dietary protein found in the gluten of wheat, rye, barley and some varieties of oats. 1,2 The incomplete proteolysis of 33-mer in humans was demonstrated by an analysis of human stool and urine, of subjects under glutencontaining diet, by using different ELISA methods. 3 It has been found that the 33-mer is the immunodominant peptide that triggers the adaptive immune response in celiac disease 4 , but the early events of the disease, as well as the role of 33-mer in other gluten-related disorders, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of well-established amylogenic diseases, different modelling approaches were applied to their studies, such as 2 | J. Name., 2012, 00, [1][2][3] This journal is © The Royal Society of Chemistry 20xx…”
Section: Introductionmentioning
confidence: 99%